Merintis Wisata Tematik Edukasi Kopi di Bali Utara sebagai Pemulihan Ekonomi Pasca-Pandemi Covid-19 - Francisca Titing Koerniawaty; I Made Sudjana (Pusat Kajian Bali Universitas Udayana, 2022)
This study was to design a coffee education thematic tourism model which could be implemented in Bongancina village as well as in other villages that have similar potential in North Bali. The model was designed by R&D research approach by collecting the data through participatory observations in January, March and September 2021. In-depth interviews and FGDs were also conducted in obtaining the village potencies. The results indicated that a coffee education thematic tourism model was designed by considering the concepts of 4A and CI which included of two coffee education thematic and four additional tour packages which were specified into forty-four tourist attraction criterias. The six tour packages included Bongancina Coffee Skills Program, Bongancina Hidden Coffee Bar by the River, Bongancina Cooking Class, Bongancina Culture Class, Bongancina Adventure, and Bongancina wellness. This model gives spacious rights to villagers to be directly involved in every tourism activity in recovering economy the post-pandemic Covid-19.